2023
DOI: 10.3390/jpm13020275
|View full text |Cite
|
Sign up to set email alerts
|

Is the Non-Coding RNA miR-195 a Biodynamic Marker in the Pathogenesis of Head and Neck Squamous Cell Carcinoma? A Prognostic Meta-Analysis

Abstract: Head and neck squamous cell carcinoma (HNSCC) represents a heterogeneous group of neoplasms whose histological derivation comes from the mucous membranes lining the epithelium: the oral cavity, the larynx, the hypopharynx, the nasopharynx, and the oropharynx. The etiopathogenetic mechanisms involving tumor genesis including the alteration of cell proliferation, apoptosis, invasion, migration, and death may involve alterations in the expression of microRNA (miR). To date there have been no systematic reviews wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…In light of the data reported in the medical literature, and from the preliminary research conducted in the field [6][7][8][9]13,14,119], we carried out our review after registering it on Prospero, which was written following the indications of PRISMA. A meta-analysis of the data was not carried out due to the excessive heterogeneity of data and histological subtypes of HNSCCs, and thus a TCGA analysis was instead used to test possible microRNA biosignatures that emerged from the data extraction and qualitative analysis of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of the data reported in the medical literature, and from the preliminary research conducted in the field [6][7][8][9]13,14,119], we carried out our review after registering it on Prospero, which was written following the indications of PRISMA. A meta-analysis of the data was not carried out due to the excessive heterogeneity of data and histological subtypes of HNSCCs, and thus a TCGA analysis was instead used to test possible microRNA biosignatures that emerged from the data extraction and qualitative analysis of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic reviews included were the following: Dioguardi et al, 2023 [9]; Dioguardi et al, 2022 [13]; Dioguardi et al, 2022 [14]; Dioguardi et al, 2022 [8]; Dioguardi et. al, 2022 [6]; Dioguardi et al, 2022 [7]; Irimie-Aghiorghiese et al, 2019 [15]; Lubov et al, 2017 [16]; Xie and Wu, 2017 [17]; Wang et al, 2019 [18]; Li et al, 2019 [19]; Qiu et al, 2021 [20]; Huang et al, 2021 [21]; Jamali et al, 2015 [22]; and Troiano et al, 2018 [23].…”
Section: Data Characteristics: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies examine the role of miRNA in various cancers, such as pancreatic [ 18 ], colon [ 19 ], prostate [ 20 , 21 ], renal [ 22 ], bladder [ 23 ], breast [ 24 ], cervical [ 25 ], ovarian [ 26 ], lung [ 27 ], and HNSCC [ 28 ]. To date, analyses of the role of miRNAs in HNSCC pathogenesis are focused generally on studies of miRNAs, such as miR-375, miR-1234, miR-103, miR-638, miR-200b-3p, miR-191-5p, miR-24-3p, miR-572, miR-483-5p, miR-20a, miR-22, miR-29a, miR-29b, mir-let-7c, miR-17, miR-374b-5p, miR-425-5p, miR-122, miR-134, miR-184, miR 191, miR-412, miR-512, miR-8392, miR-21, miR-31, miR-155, miR-196a, miR-196b, miR-9, miR-29c, miR-223, miR-187, Let-7a, miR- 27, miR-34, miR-92, miR-124, miR-125a, miR-136, miR-139, miR-145, miR-146a, miR-200, miR-195, and miR-205 [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the miR-196 family [ 20 ] and miR-155 [ 21 ] have been identified as potential predictive indicators of survival for HNSCC. Besides, Dioguardi et al [ 22 ] showed the underexpression of miR-195 in patients with HNSCC and its excellent potential as an independent prognostic survival marker for HNSCC.…”
Section: Introductionmentioning
confidence: 99%